EVALUASI PENERAPAN PENATAUSAHAAN BARANG MILIK DAERAH PADA BPK-BMD KABUPATEN MINAHASA UTARA - Manurung, Lucky Jansen; Sondakh, Jullie J.; Budiarso, Novi S. (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
Regional-Owned Assets Administration (BMD) by Badan Pengelola Keuangan dan Barang Milik Daerah (BPK-BMD) Kabupaten Minahasa Utara conducted by following Permendagri No. 19 Tahun 2016 about Technical guideline of Regional-Owned Assets in thus recording, inventory, and reporting processes of Regional-Owned Assets in this government region is showed well, is resulting regional balance sheet basic for BPK-BMD Kabupaten Minahasa Utara. This researchâs objective is to figure out whether the implementation of Regional-Owned Assets Administration in BPK-BMD Kabupaten Minahasa Utara has been followed Permendagri Nomor 19 Tahun 2016 and itsâ research type is descriptive analysis. This research outcome has concluded that Regional-Owned Assets in Kabupaten Minahasa Utara Government has been conducted by following Permendagri Nomor 19 Tahun 2016. BPK-BMD Kabupaten Minahasa Utara in implementing Regional-Owned Assets Administration, is based on the existed Permendagri Nomor 19 Tahun 2016 and Regional-Owned Users and Authorized Parties keep maintain this procedurs in Kabupaten Minahasa Utara.Keywords : Regional Owned Assets Management, Controlling and Monitoring.